A theoretical model of the evolution of maternal effects under parent-offspring conflict. - Uller, T; Pen, I (2011)
The evolution of maternal effects on offspring phenotype should depend on the extent of parent-offspring conflict and costs and constraints associated with maternal and offspring strategies. Here, we develop a model of maternal effects on offspring dispersal phenotype under parent-offspring conflict to evaluate such dependence. In the absence of evolutionary constraints and costs, offspring evolve dispersal rates from different patch types that reflect their own, rather than the maternal, optima. This result also holds true when offspring are unable to assess their own environment because the maternal phenotype provides an additional source of information. Consequently, maternal effects on offspring diapause, dispersal, and other traits that do not necessarily represent costly resource investment are more likely to maximize offspring than maternal fitness. However, when trait expression was costly, the evolutionarily stable dispersal rates tended to deviate from those under both maternal and offspring control. We use our results to (re)interpret some recent work on maternal effects and their adaptive value and provide suggestions for future work.